OPTIMALISASI PENYALURAN ZAKAT PRODUKTIF TERHADAP PEMBERRDAYAAN EKONOMI UMAT - Syahril, Syahril; Abrori, Faizul; Alwiyah, Alwiyah; Kurdi, Moh. (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2022)
The presence of the Amil Zakat Institution (LAZ) must be at the forefront of initiating community empowerment with the funds collected. The potential of ZIS is at least one of the important assets that has been utilized at least not only for consumptive purposes but zakat is managed productively. One of the Amil Zakat Institutions (LAZ) is NU CARE LAZISNU which has an important role as a guardian of the development of stability in society. Currently, NU CARE LAZISNU has a special program that focuses on 4 (four) pillars of the program: education, health, disaster and economic development. On this occasion, NU CARE LAZISNU implements productive zakat and is committed to providing assistance in the development, marketing, and improvement of quality and affordable products. This program provides working capital in the form of revolving capital for mustahiq. This research method uses a case study, which is one type of qualitative research with two types of data, namely primary data and secondary data. The results of the first research, Optimizing the distribution of productive zakat in empowering the economy of the people in LAZISNU East Java, namely maximizing the existence of a system of distributing assistance to the community which is not only consumptive but has also been productive in MSME capital assistance distribution in almost every district/city. Second, the strategy of empowering the people's economy through productive zakat in LAZISNU East Java, namely by using a fundraising program. The first fundraising is driven by a fixed donor coin box, and the second is digital fundraising in collaboration with kitabisa.com.